2017
DOI: 10.1111/eth.12711
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulation of female tail length did not cause differential allocation by males in the barn swallow

Abstract: The evolution and maintenance of female ornamentation has attracted increasing attention, because the previous explanation, that is a non‐functional copy of functional male ornamentation, seems insufficient to explain female ornamentation. A post‐mating sexual selection, differential allocation, may be more common than pre‐mating sexual selection, but few studies have investigated differential allocation by males. Here, we studied differential allocation of incubation investment by male barn swallows Hirundo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This explanation seems unlikely given that naturally long-tailed females show higher (rather than lower) reproductive investment (see Introduction). However, egg size decreases with female tail length at least at interspecific levels in hirundines (Hasegawa & Arai 2017) and the length of the incubation period increases with female tail length in Japanese barn swallows (Hasegawa et al 2018), both of which cannot easily be compensated by their mates (note that male barn swallows lack brood patches; Turner 2006; Voss et al 2008). Thus, male mate preference against long-tailed females might be beneficial to avoid inevitable loss of reproductive (maternal) investment in advance, though the importance of this kind of reproductive benefit might be relatively small compared to the benefit of pairing with long-tailed females (see above).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation seems unlikely given that naturally long-tailed females show higher (rather than lower) reproductive investment (see Introduction). However, egg size decreases with female tail length at least at interspecific levels in hirundines (Hasegawa & Arai 2017) and the length of the incubation period increases with female tail length in Japanese barn swallows (Hasegawa et al 2018), both of which cannot easily be compensated by their mates (note that male barn swallows lack brood patches; Turner 2006; Voss et al 2008). Thus, male mate preference against long-tailed females might be beneficial to avoid inevitable loss of reproductive (maternal) investment in advance, though the importance of this kind of reproductive benefit might be relatively small compared to the benefit of pairing with long-tailed females (see above).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted this “sequential choice” test rather than the “simultaneous choice” test, because the former is more appropriate than the latter in the barn swallow, a protandry migrant species, in which males encounter females sequentially rather than simultaneously as in many other species (Barry & Kokko 2010). Because long-tailed females are high-quality females in terms of arrival date, survivorship, breeding experience, and parental and reproductive investment in barn swallows including Japanese populations (e.g., Møller 1993a, 1994; Brown & Brown 1999; Hasegawa et al 2016b, 2017, 2018, 2020), and because previous correlational studies support sexual selection for female long tails in Japanese barn swallows (Hasegawa et al 2017), we predicted that males would prefer tail-elongated female models to control female models. We also examined individual mate preference for female tail length in relation to male tail length, which is virtually impossible to examine when using indirect measures of mate preference (e.g., breeding date, assortative mating; see above).…”
Section: Introductionmentioning
confidence: 99%
“…residual body mass against keel length; n = 20, coefficient ± se = 4.75 ± 2.07, F 1,19 = 5.25, P = 0.03; Arai et al ). Although female tail length was manipulated at capture (control and tail‐shortened) as part of another investigation, this manipulation had no detectable effect on male incubation investment (Hasegawa et al ), and thus we pooled data regardless of treatment. Although we captured three males a few days after capturing females (2, 3 and 12 days, all of which were captured after nest observation), excluding these three males from our dataset did not qualitatively change the results (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that 60 min of observation is long enough to characterize male incubation patterns (e.g. Hasegawa et al ). When re‐analysing data from 120‐min observation periods (Hasegawa et al ), presence/absence of male incubation during 60 min of observation correctly predicted presence/absence of male incubation over 120 min (83%, 20 out of 24 males; note that male and female incubation did not vary systematically during the incubation period; Hasegawa et al ).…”
Section: Methodsmentioning
confidence: 99%
“…In the barn swallow, many correlational studies suggest that sexual selection drives the evolution of long female tails (e.g., Møller, 1993a, 1994; see Hasegawa et al, 2017 for Japanese barn swallows), but the results of manipulative experiments on female tails do not support sexual selection for long female tail feathers (Cuervo et al, 1996; see also Hasegawa et al, 2018, 2020 for no detectable differential allocation). However, assuming that female tail length would attract mates, as is the case for male tail length (see previous paragraph), all these studies used indirect measures of mate preferences.…”
Section: Introductionmentioning
confidence: 99%